Development of a Health-Related Quality of Life Questionnaire (HRQL) for patients with Extremity Soft Tissue Infections (ESTI) - Storck, Aric J; Laupland, Kevin B; Read, Ronald R; Mah, Manuel W; Gill, John M; Nevett, Deborah; Louie, Thomas J (BMC infectious diseases, 2006)
Past clinical trials of antimicrobial treatment in soft tissue infections have focused on non-standardized clinical and physiological outcome variables, and have not considered the subjective experience of patients. The objective of this study was to develop a health-related quality of life questionnaire (HRQL) for patients with extremity soft tissue infections (ESTI) for future use in clinical trials. The design of this study followed published guidelines and included item generation, item reduction, and questionnaire preparation. Study subjects were consenting English-speaking adults with acute ESTI requiring prescription of at least two days of outpatient intravenous antibiotic therapy. A list of 49 items that adversely impact the quality of life of patients with ESTI was generated by literature review, informal health professional feedback, and semi-structured interviews with twenty patients. A listing of these items was then administered to 95 patients to determine their relative importance on quality of life. A questionnaire was prepared that included the twenty most important items with a 5-point Likert scale response. Questionnaire domains included physical symptoms, problems performing their activities of daily living, impairment of their emotional functioning, and difficulties in their social interactions as related to their ESTI. The final questionnaire was pre-tested on a further ten patients and was named the ESTI-Score. The ESTI-Score is a novel instrument designed to quantify the impact of ESTI on quality of life. Future study is required to determine its validity and responsiveness before use as an outcome measure in clinical trials.